Too-Simple Ceremony Marks Tony Williams' 70th - Joseph, Terry (Express)
A small crowd turned out to celebrate the 70th birthday of Pan Legend Anthony ‘Tony’ Williams. Williams who took no more than six months of formal music lessons, went on to become a composer from as early as 1956. In 1974 he wrote the famous “Pan Down Fifth Avenue” as a memorial of a tour to New York by Pan Am North Stars. William’s is credited with the invention of the ‘Spiderweb pan’. This pan was the first attempt at locating notes in the fourths and fifths sequence. He also introduced the double-cello pan.
Keywords: Composers -- Trinidad and Tobago; Steel drum (Musical instrument) -- Trinidad and Tobago; Inventors -- Trinidad and Tobago